2020
DOI: 10.3390/met10070978
|View full text |Cite
|
Sign up to set email alerts
|

Bioleaching of Phosphate Minerals Using Aspergillus niger: Recovery of Copper and Rare Earth Elements

Abstract: Rare earth elements (REE) are essential in high-technology and environmental applications, where their importance and demand have grown enormously over the past decades. Many lanthanide and actinide minerals in nature are phosphates. Minerals like monazite occur in small concentrations in common rocks that resist weathering. Turquoise is a hydrous phosphate of copper and aluminum scarcely studied as copper ore. Phosphate-solubilizing microorganisms are able to transform insoluble phosphate into a more soluble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Other studies reported that the highest percentages of bioleached total RE from monazite and (Th-U) concentrate directly by Aspergillus ficuum, are found to be 75.4 and 63.8% at a pulp density 0.6 and 1.2% (w/v), respectively, after 9 days and 63.5 and 52.6% by Pseudomonas eruginosa after 8 days (Hassanien et al, 2014). Also, fungal strains able to solubilize phosphate minerals such as A. niger have shown potential for RE bioleaching from monazite (Castro et al, 2020). Several other fungal strains have been also used to leach monazite releasing RE to the aqueous phase such us Aspergillus terreus, Paecilomyces spp.…”
Section: Mobilization Of Rare Earth By Rhizosphere Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies reported that the highest percentages of bioleached total RE from monazite and (Th-U) concentrate directly by Aspergillus ficuum, are found to be 75.4 and 63.8% at a pulp density 0.6 and 1.2% (w/v), respectively, after 9 days and 63.5 and 52.6% by Pseudomonas eruginosa after 8 days (Hassanien et al, 2014). Also, fungal strains able to solubilize phosphate minerals such as A. niger have shown potential for RE bioleaching from monazite (Castro et al, 2020). Several other fungal strains have been also used to leach monazite releasing RE to the aqueous phase such us Aspergillus terreus, Paecilomyces spp.…”
Section: Mobilization Of Rare Earth By Rhizosphere Bacteriamentioning
confidence: 99%
“…and Penicillum sp. that can release a total concentration of 12.32 mg/L RE (Ce, La, Nd, and Pr) from the weathered monazite after 8 days (Castro et al, 2020). Another study with A. niger reported that the highest rates of RE from monazite were obtained when the fungus was cultivated on minimal medium with the mineral as the sole phosphorous source.…”
Section: Mobilization Of Rare Earth By Rhizosphere Bacteriamentioning
confidence: 99%
“…Most of the REE bioleaching studies that have been developed have treated mineral ores with a variety of microorganisms. Phosphate-solubilizing microorganisms are particularly relevant in the bioleaching of monazite because they transform insoluble phosphate into more soluble phosphorous forms [3,23,24]. The mineral phosphate solubilization occurs through the biological generation of organic acids and the proton substitution reaction:…”
Section: Biorecovery Of Rees From Industrial and Electronic Wastementioning
confidence: 99%
“…The transition from fossil fuels to renewable energy and the development of new technologies have increased the mining of strategic metals and nonconventional minerals. Castro et al [5] investigated the dissolution of heavy metals from phosphate minerals (aluminum phosphate, turquoise, and monazite) using the fungus Aspergillus niger. A. niger was able to reach 8.81 mg/L of copper and up to 1.37 mg/L of REE in the aqueous phase.…”
Section: Bioleachingmentioning
confidence: 99%